In Vitro Hepatitis C Virus Infection and Hepatic Choline Metabolism - Gobeil Odai, Kaelan (Viruses, 2020)
Choline is an essential nutrient required for normal neuronal and muscular development, as well as homeostatic regulation of hepatic metabolism. In the liver, choline is incorporated into the main eukaryotic phospholipid, phosphatidylcholine (PC), and can enter one-carbon metabolism via mitochondrial oxidation. Hepatitis C virus (HCV) is a hepatotropic positive-strand RNA virus that similar to other positive-strand RNA viruses and can impact phospholipid metabolism. In the current study we sought to interrogate if HCV modulates markers of choline metabolism following in vitro infection, while subsequently assessing if the inhibition of choline uptake and metabolism upon concurrent HCV infection alters viral replication and infectivity. Additionally, we assessed whether these parameters were consistent between cells cultured in fetal bovine serum (FBS) or human serum (HS), conditions known to differentially affect in vitro HCV infection. We observed that choline transport in FBS- and HS-cultured Huh7.5 cells is facilitated by the intermediate affinity transporter, choline transporter-like family (CTL). HCV infection in FBS, but not HS-cultured cells diminished CTL1 transcript and protein expression at 24 h post-infection, which was associated with lower choline uptake and lower incorporation of choline into PC. No changes in other transporters were observed and at 96 h post-infection, all differences were normalized. Reciprocally, limiting the availability of choline for PC synthesis by use of a choline uptake inhibitor resulted in increased HCV replication at this early stage (24 h post-infection) in both FBS- and HS-cultured cells. Finally, in chronic infection (96 h post-infection), inhibiting choline uptake and metabolism significantly impaired the production of infectious virions. These results suggest that in addition to a known role of choline kinase, the transport of choline, potentially via CTL1, might also represent an important and regulated process during HCV infection.